The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/pr10061131
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Herbal Medicines for Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive interstitial lung scarring condition with the histological characteristic of typical interstitial pneumonia. Injury to alveolar epithelial cells is a critical precursor in the pathogenesis of this disease. The prevalence of IPF is growing exponentially, with substantial morbidity and mortality rates increasing the burden on economic healthcare costs. A multidisciplinary approach for diagnosis is used to rule out the alternative causes of interstitial lung di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…In studies for the treatment of PF, natural medicines such as herbs have shown low adverse effects, stable anti-inflammatory and anti-fibrotic therapeutic effects and no significant drug dependence due to their natural properties. This makes them a promising therapeutic target for PF [ 42 ]. Jiang et al [ 43 ] took advantages of the ball milling technique to prepare a salvianolic acids dry powder inhalation complex with l -arginine and lecithin.…”
Section: Lipid-based Delivery Systemmentioning
confidence: 99%
“…In studies for the treatment of PF, natural medicines such as herbs have shown low adverse effects, stable anti-inflammatory and anti-fibrotic therapeutic effects and no significant drug dependence due to their natural properties. This makes them a promising therapeutic target for PF [ 42 ]. Jiang et al [ 43 ] took advantages of the ball milling technique to prepare a salvianolic acids dry powder inhalation complex with l -arginine and lecithin.…”
Section: Lipid-based Delivery Systemmentioning
confidence: 99%
“…5 Hence, there is a need to discover new drugs for IPF and the most recent trends in literature for herbal products with multitargeted approaches. [6][7][8] The network pharmacology tools are used to interpret Chinese traditional drugs for their mechanistic activity in IPF, such as Fei-Xian Formula, 9 Qingfei oral liquid, 10 Baofeikang Granules, 11 Astragalus Polysaccharide, 12 Isorhynchophylline, 13 and Platycodon grandiflorum. 14 The major pharmacological activity of these drugs is inhibiting TGF-β, multi-targeted molecular modulation of inflammation and antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…This collection of studies encompasses two review papers that delve into distinct research areas. The first review paper examines the potential therapeutic application of herbal medicines, specifically Traditional Chinese Medicine (TCM), in the context of idiopathic pulmonary fibrosis (IPF), a progressive pulmonary disorder characterized by fibrotic lung tissue [1]. The review highlights the anti-inflammatory and anti-fibrotic properties of herbal medicines, shedding light on their potential as a promising therapeutic target for IPF.…”
mentioning
confidence: 99%